Carcass Characteristics of Broilers Fed Sugarcane Press Residue with Biotechnological Agents - Suresh, B.N.; Reddy, B.S.V.; B.H., Manjunatha Prabhu; Jaishankar, N. (International Journal of Poultry Science, 2009)
An experiment was carried out to study the effect of inclusion of sun-dried Sugarcane Press Residue (SPR) as a feed ingredient with some biotechnological interventions on the carcass characteristics and gut development of broilers. Experimental diets were prepared by incorporating SPR at 0, 5 and 10 per cent and further such diets were supplemented with or without lipid utilizing agents (lipase and lecithin) or NSP degrading enzymes or together to result in a set of 12 diets. Each diet prepared for starter (0-14 days), grower (15-28 days) and finisher (29-42 days) phases was offered to triplicate groups of 10 broiler chicks each. At the termination of the experiment (42nd day), no significant (p>0.05) differences in dressing percentage, meat to bone ratio, abdominal fat and relative weights of different organs viz., liver, heart, gizzard, proventriculus and spleen excepting bursa (p<0.01) among different treatments. The main factor SPR showed significant (p<0.01) differences in abdominal fat (27.79, 22.60 and 19.13 g/bird or 1.81, 1.47 and 1.33% of live weight in 0, 5 and 10% SPR based groups) while the main factor biotechnological agents in relative weight of spleen, but not for other parameters. The relative length of different segments of small intestine viz., duodenum, jejunum and ileum of birds under different treatments and main factors were remained statistically (p>0.05) similar. Thus it was implied that the carcass characteristic of broilers remained unaffected by SPR inclusion up to 10% except abdominal fat, gizzard and proventriculus and by supplementation of some biotechnological agents except spleen.